Disparities in Vulvar Cancer Reported by the National Cancer Database: Influence of Sociodemographic Factors. Issue 4 (October 2015) - Chase, Dana M.; Lin, Chun Chieh; Craig, Christine D.; Fedewa, Stacey A.; Virgo, Katherine S.; Farley, John H.; Halpern, Michael; Monk, Bradley J.
Abstract : OBJECTIVE: To assess whether there is an association of patient sociodemographic factors with stage at diagnosis, treatment, and overall survival in patients with vulvar cancer in the National Cancer Database. METHODS: This was a retrospective cohort study of patients with primary squamous vulvar carcinoma identified from the National Cancer Database (1998–2004). Multivariate logistic regression was conducted to examine risk factors associated with advanced-stage (stage III or IV) disease at diagnosis. Multivariable Cox regression models were performed to explore risk factors associated with 5-year all-cause mortality. RESULTS: Of 11, 153 patients, 42.3% (n=4, 713) were diagnosed with stage I disease, 24.6% (n=2, 745) stage II, 22.9% (n=2, 556) stage III, and 10.2% (n=1, 139) stage IV. Advanced stage was significantly associated with older age, nonprivate insurance, and treatment at a lower case volume center ( P <.01). Of note, roughly 30% of patients with advanced-stage disease did not receive radiation therapy. Within the advanced stages, age 60 years or older and insurance type were associated with decreased survival ( P <.01). In stage III disease, only black race and treatment at a community hospital were associated with a lower risk of death ( P <.01). CONCLUSION: Patient sociodemographic and clinical characteristics are significantly associated with vulvar cancer stage presentation, treatment, and survival. Unfortunately, within this disease, surgical approaches and adjuvant radiation do not appear consistent. LEVEL OF EVIDENCE: II Abstract : In vulvar cancer, health disparities exist in presentation and outcomes, whereas treatment rendered appears to be heterogeneous and inconsistent.